The modern approaches to the description of the spatial data at control of electronic district maps - Лисицин, Владимир Эдуардович; Побережный, Андрей Анатольович; Горелышев, Станислав Анатольевич (Eastern-European Journal of Enterprise Technologies, 2010)
Some approaches realized in Visual Studio within NET-technologies are being revealed and effectively describe the spatial data of geoinformation systems. Necessity of strict typification and standardization of representation of a metainformation for the spatial data is proved.